Caracteristics, Diagnosis, Management and Output of Persistent Pulmonary Hypertension of the Newborn at Dr. Soetomo Hospital - Mardiyan Aprianto1 , Mahrus A Rahman1 , Martono Tri Utomo1 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background Persistent pulmonary hypertension of the new-born (PPHN) is a failure of lung circulation innew-born. However the data related the characteristics of clinical profile, diagnostic, management and theoutcome was still limited.Objective To investigated the characteristics, diagnostics, management and outcome from PPHN.MethodsRetrospective observational study. Neonates with PPHN from January 2015 to December 2019 wereidentified from medical record. After the data was excluded, the characteristics, diagnostic, management andthe outcome was collected. The statistical analysis to known the frequency and the chi-square test used toanalyse the association between the treatment and the outcomes (P < 0.05).Results 37 medical records enrolled the study, with the characteristics; 62.2% babies was boy, 70.3% withterm infant, 70.3% with normal birth weight, 24.3% with maternal history of eclampsia. 62.2% babiesborn by C-section, 21.9% with history of asphyxia and MAS. 78.4% with differences between pre- andpost-ductal saturation. From echocardiography result, 13.5% diagnosed as mild PPHN, 54.1% as moderatePPHN and 32.4% severe PPHN. From the management consisted of 5.4% with O2 nasal, 32.4% O2 CPAPand 62.2% O2 ventilator, 24.3% with sildenafil, 5.4% with combination sildenafil and illoprost, 5.4% withcombination sildenafil, illoprost, and surfactant, 2.7% with combination sildenafil, illoprost, surfactant,and inotropic, 24.3% with combination sildenafil, illoprost, and inotropic, and 37.8% with combinationsildenafil and inotropic. The outcomes was obtained 35.1% babies was died and 64.9% babies was cured,with oxygenation supplementation had significantly affecting the outcomes (P=0.02)Conclusion The characteristics of PPHN was dominated by baby boy, term infant and good birth weight,history of asphyxia and MAS, maternal history of eclampsia, C-section delivery and the differences betweenpre- and post-ductal saturation. The diagnosis commonly with moderate PPHN. The management with O2ventilator and combination sildenafil-inotropic. The outcome mostly the babies was cured.